Realitas Masyarakat Papua dalam Distorsi Representasi Media: Analisis Media Baru - Logan Gunadi Wirawan; Muhammad Fauzan Farendra; Yoas Lintang (Jurnal HAM, 2022)
Media portrayals towards minorities result in implications towards how society as a whole views them. This paper questions how the media representation of Papua reflects the reality of their socio-political situation and what the implications of said representations are. Based on secondary data analysis towards Indonesian media's portrayals of Papua, including but not limited to its' constituents and environment, this paper seeks to understand based on new media theories of social reality how the media portrayals of Papua have impacts towards the socio-political experience of Papuans in Indonesians, and Indonesians towards Papuans. The results obtained by the analysis indicate that media employs stereotypical and surface level portrayals of Papua in a way that dismisses the structural issues Papuans are facing. Those results show that media representation plays an integral part towards manufacturing discrimination towards Papuans, leading towards this paper's recommendations that calls for increased pressure towards demanding that the damages caused by false media portrayals of Papua were to be rectified by responsible parties.